Why do Adolescents Lose Their Sense of Guilt ? A Scoping Review of Antecedents of Moral Disengagement in Offline and Online Aggressive Behaviors - Airawan, Ratra Adya; Hasanati, Nida (Jurnal Indonesia Sosial Sains, 2026)
Moral detachment is an important cognitive mechanism that allows a person to commit aggressive actions without feeling personal sanctions or guilt. This study aims to describe and compile various factors before the occurrence of moral detachment in adolescents and young adult individuals using a broad study approach. A total of 23 scientific articles from international and local publication databases between 2020 and 2025 were analyzed thematically. The results of the data aggregation show that moral release is influenced by interactions involving many factors that include individual, social, digital environment, as well as organizational aspects. Intrapersonal traits such as dark personality traits (Dark Triad), anger traits, and low self-control abilities emerged as main indicators. On the environmental side, the weakness of parental bonds, friendship status, exposure to violent media, and a loose school atmosphere significantly accelerate the emergence of moral detachment.